Examination Of The Interplay Among Legal Risks-Related Issues, Risk Management Practices, And Construction Project Performance: In The Case Of Addis Ababa Public Buildings Construction Projects - Lami, Fufa (ASTU, 2025)
Legal Risks Were Significant Issues In Ethiopia's Public Buildings Construction Projects. Several Studies Have Addressed This Issue Previously, But There Was A Lack Of Modeling The Interrelationship, And Many Public Buildings Construction Sectors In Addis Ababa Continue To Face Legal Challenges And Inadequate Legal Risk Management Strategies. Therefore, This Study Aims To Fill This Gap By Examining The Direct And Indirect Interrelationship Between Legal Risk Related Issues, Legal Risk Management Strategies, And Construction Project Performance By The Pls-Sem Framework At The 36 Public Buildings Construction Projects In Addis Ababa, Ethiopia. A Hypothesis Was Drawn To Test This Interrelationship, And A Theoretical Model Was Developed Based On The Literature. Mixed-Method Approaches Would Be Used In This Study. The Purposive And Stratified Sampling Methods Were Used. The Data Gathering Was Closed-Ended Structured Questionnaires, Quantitative Insights Using By 5 Likert Scale From Strongly Disagree To Strongly Agree. The 95 Respondents Were Selected Based On Proportionate Stratified Random Sampling. Stakeholders Were Categorized Based On Their Roles And Importance To Legal Risk-Related Issues In The 36 Public Building Construction Projects Using A Purposive And Stratified Sampling Technique Out Of 126 Total Population. In This Study, The Two Data Collection Methods Used Were Primary And Secondary. The Primary Data Would Be Collected Through Closed-Ended Structured Questionnaires, Document Analysis, And Personal Interviews. The Collected Data Were Prepared For Analysis Using Spss Version 27 Analytical Software. The Analysis Was Conducted Using Partial Least Squares Structural Equation Modeling. The Results Of The Study Show That Dispute Resolution And Litigation Risks, Contractual And Financial Risks, Force Majeure, Environmental, And Labor Risks, Of Legal Risks-Related Issues Have The Highest Impact On The Performance Of A Project. The Results Indicated That Dispute Resolution And Litigation Risk Factors Were Found To Have A Path Coefficient Beta Of 0.967, The Highest Impact In Comparison With Other Legal Risk Factors Issues. When It Comes To The Legal Risk Management Strategies, Financial And Insurance Risk Management Strategies, And Stakeholder, Community Legal Management Had A Major Impact And Contribution To The Performance Of Projects. The R?? Value Results Show That Legal Risks And Management Practices Explain 35.1% Of The Variation In Project Performance.
Keywords: Legal Risks-Related Issues, Risk Management Strategies, Project Performance, And Pls-Sem